The impact of hyperinsulinemia on short-term prognosis in patients with hypertriglyceridemia-induced acute pancreatitis - Wang, Mengjun; Zheng, Lei; Qian, Long; Xu, Maoqi (Frontiers in Endocrinology, 2025)
PurposeThe short-term prognosis of hyperinsulinemia in patients with hyperlipidemia resulting in acute pancreatitis remains uncertain, so this research explores the correlation between them.Material and methodsThis study retrospectively analyzed patients treated for hypertriglyceridemic acute pancreatitis at Wuhu Hospital of Traditional Chinese Medicine between January 2020 and April 2023. Patients were divided into two groups based on laboratory diagnosis: the hyperinsulinemia group (HINS) and the non-hyperinsulinemia group (NHINS). The study aims to evaluate the short-term effects of hyperinsulinemia on acute pancreatitis.ResultsA total of 92 patients with Hypertriglyceridemic pancreatitis were included in the study before receiving lipid-lowering therapy, with 44 in the HINS group and 48 in the NHINS group. Significant differences were observed between the two groups in terms of white blood cell count (WBC), hypersensitive C-reactive protein (CRP) levels, and fasting blood glucose at 2, 3-4, and 5–7 days after initiation of lipid-lowering intervention (P < 0.05). Following admission, patients received symptomatic interventions. However, there was a significant difference in the rate of decrease compared to the baseline between the fifth and seventh days (P < 0.05). Additionally, the groups showed significant differences in the readmission rates for recurrent pancreatitis within 30 days post-ICU transfer and discharge (P < 0.05). No statistically significant distinctions were noted in the length of hospital stay or quality of life scores fifteen days post-discharge.ConclusionHyperinsulinemia adversely affects the recovery process of patients with Hypertriglyceridemia-induced acute pancreatitis.